Effect of Lymphatic Drainage Manipulation on Knee Joint Swelling after Anterior Cruciate Ligament Reconstruction - MENG Cong; BAO Yong; ZHANG Weiming (康复学报)
ObjectiveTo analyze the effect of lymphatic drainage manipulation on knee joint swelling after anterior cruciate ligament (ACL) reconstruction.MethodsThis prospective study was conducted to select patients with ACL injury admitted to the Orthopaedics Department of Shanghai Ruijin Rehabilitation Hospital from February 2020 to February 2023. The participants were divided into the observation group and control group according to the random number table method, with 120 cases in each group. ACL reconstruction was performed in both groups. Postoperatively, the control group was treated with ice compression, and the observation group was treated with lymphatic drainage manipulation. Both groups received continuous intervention for 4 weeks. The swelling degree and skin temperature of knee joint were observed at different time points (postoperative day, 1 week, 2 weeks and 4 weeks postoperatively). Range of motion (ROM) and knee function [Lysholm knee score scale (LKSS)] before and after intervention for both groups were observed, as well as changes in pain substances [substance P, 5-hydroxytryptamine (5-HT)] and inflammatory markers [tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6)].ResultsThe swelling degree of knee joint in the observation group was lower than that in the control group at 1, 2 and 4 weeks postoperatively (P<0.05). The partial regression coefficient showed that at 1, 2 and 4 weeks postoperatively <alternatives><mover accent="true">β^</mover> <?fx-imagestate width="1.60866666" height="3.72533321"?> <?fx-imagestate width="1.60866666" height="3.72533321"?> </alternatives>=-2.800, -1.760, -0.890 respectively, with P<0.001, indicating a reduction of knee joint swelling in the observation group at 1, 2 and 4 weeks postoperatively compared to the postoperative day. The observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively <alternatives><mover accent="true">β^</mover> <?fx-imagestate width="1.60866666" height="3.72533321"?> <?fx-imagestate width="1.60866666" height="3.72533321"?> </alternatives>=-1.070, -0.880, -0.600, P=0.003, 0.003, 0.048, respectively. The observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively were lower than the control group, that is, the observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively were lower than the postoperative day; The skin temperature of knee joint in the observation group was lower than that in the control group at 1, 2 and 4 weeks postoperatively (P<0.05); the interpretation of partial regression coefficient: at 1, 2 and 4 weeks postoperatively <alternatives><mover accent="true">β^</mover> <?fx-imagestate width="1.60866666" height="3.72533321"?> <?fx-imagestate width="1.60866666" height="3.72533321"?> </alternatives>=-0.090, -0.130, -0.520, P<0.05, indicating that the skin temperature of knee joint in the observation group at 1, 2, 4 weeks postoperatively was lower than that on the postoperative day; the observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively <alternatives><mover accent="true">β^</mover> <?fx-imagestate width="1.60866666" height="3.72533321"?> <?fx-imagestate width="1.60866666" height="3.72533321"?> </alternatives>=-0.193, -0.330, -0.187, P<0.001, the observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively decreased by 0.193, 0.330, 0.187 ℃ compared with the control group, that is, the observation group*1 week postoperatively, the observation group*2 weeks postoperatively, the observation group*4 weeks postoperatively decreased compared with the postoperative day. After the intervention, ROM and LKSS in the two groups were higher than those before intervention, with the observation group higher than the control group (P<0.05). After the intervention, the level of substance P and 5-HT in the two groups was lower than those before intervention, and the observation group was lower than the control group (P<0.05). After the intervention, the level of TNF-ɑ and IL-6 in the two groups was lower than those before intervention, and the level in the observation group was lower than those in the control group (P<0.05).ConclusionLymphatic drainage maneuvers are more effective than ice compress in improving postoperative knee joint swelling, lowering knee skin temperature, reducing postoperative pain, and promoting recovery of knee function in patients undergoing ACL reconstruction.